Job satisfaction and subjective well-being among Czech nurses - Gurková, Elena; Haroková, Sylvie; Džuka, Jozef; Žiaková, Katarína (International journal of nursing practice, 2014)
The aim of the present study was to investigate the relationship between domains of the job satisfaction and components of subjective well-being in nurses. A convenience sample of hospital nurses was recruited from six hospitals in Czech Republic. Data were collected using a set of questionnaires that included the McCloskey/Mueller Satisfaction Scale, the Positive Affect Scale, the Negative Affect Scale and the Personal Well-being Index. We confirmed low association between job satisfaction and subjective well-being of nurses. Satisfaction with extrinsic rewards, co-workers and family/work balance accounted for only a small percentage of variance in cognitive component of subjective well-being. Positive affect was predicted by interaction opportunities and scheduling. Negative affect was predicted by interaction opportunities and scheduling and intention to leave the actual workplace. Low percentage of the variance suggests that subjective well-being is not strongly influenced by job satisfaction.
Keywords: subjective well-being; dospělí; pracovní uspokojení; job satisfaction; Adult; mladý dospělý; lidé; nursing; personál sesterský; Middle Aged; Aged; Czech Republic; Job Satisfaction; Young Adult; Česká republika; lidé středního věku; senioři; Nursing Staff; spillover; Humans